1995
DOI: 10.3109/10401239509149622
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Clozapine Discontinuation Among 805 Patients in the VA Hospital System

Abstract: The goal of this study was to determine if demographic or clinical factors collected at baseline on patients treated with clozapine would increase the risk of having clozapine discontinued for (a) lack of response, (b) side effects, (c) noncompliance, (d) concomitant illness, or (e) death. The subjects were 805 patients treated with clozapine at 96 Department of Veterans Affairs Hospital System facilities. Multiple logistic regression was used to determine if any of the baseline variables predisposed patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 0 publications
6
42
0
Order By: Relevance
“…This finding is not surprising, because previous work has consistently shown that black patients are less likely than white patients to be given a prescription for clozapine and more likely to have clozapine therapy discontinued (10). This finding is not surprising, because previous work has consistently shown that black patients are less likely than white patients to be given a prescription for clozapine and more likely to have clozapine therapy discontinued (10).…”
Section: Discussionmentioning
confidence: 84%
“…This finding is not surprising, because previous work has consistently shown that black patients are less likely than white patients to be given a prescription for clozapine and more likely to have clozapine therapy discontinued (10). This finding is not surprising, because previous work has consistently shown that black patients are less likely than white patients to be given a prescription for clozapine and more likely to have clozapine therapy discontinued (10).…”
Section: Discussionmentioning
confidence: 84%
“…It is possible that because of lower baseline white blood cell counts, African Americans may have been subjected to more frequent laboratory testing than whites taking clozapine, adversely affecting patient compliance. 59,60 It is also possible that, because of perceptions of concomitant substance abuse disorders or a history of noncompliance, physicians may have been less likely to prescribe this medication to African Americans and Hispanics. 59 Two studies 59,60 reported that African Americans were more likely to discontinue clozapine therapy than whites, but whether changes in therapy were initiated by the patient or physician was not measured.…”
Section: Covariates and Atypical Antipsychotic Prescriptionsmentioning
confidence: 99%
“…It is therefore notable that we did not find racial differences in clozapine’s effectiveness relative to other antipsychotics given evidence that clozapine-treated blacks receive lower doses (17), experience more weight gain (23), and have a higher likelihood of having clozapine unnecessarily discontinued by their physicians (17, 24, 25). …”
Section: Discussionmentioning
confidence: 75%